Jump To Box Kombinasi Core Plank Knee To Elbow Terhadap Power Otot Tungkai - Triyanita, Maya (Jurnal Fisioterapi Terapan Indonesia, 2024)
Leg power training is defined as a movement to get the jump in athletes doing the maximum jump smash. Badminton requires leg muscle explosive power because it is the muscle's ability to overcome loads and with a high speed of contraction. This study aims to determine differences in the effect of jump to box training, a combination of core plank knee to elbow on increasing leg power in badminton athletes. This study used an experimental design method with a pre-test and post-test design. The treatment group was given the Jump To Box Combination Core Plank Knee To Elbow exercise. The number of each group was 13 and each group was given exercise 3 times a week for 6 weeks. Measurement of leg muscle power in badminton athletes with the Vertical Jump Test. The value of the study showed that in the group with increased leg muscle power, the pre-test mean value was 34.69 ± 5.46, which increased to 38.38 ± 5.72 during the post test and obtained a value of p = 0.000 (p <0.05). It was concluded that giving Jump To Box training in combination with Core Plank Knee To Elbow can increase leg muscle power in badminton athletes.